Diagnostic value of upper airway morphological data based on CT volume scanning combined with clinical indexes in children with obstructive sleep apnea syndrome - Shi, Yanmin; Gu, Meilan; Zhang, Xin; Wen, Mengmeng; Li, Runhua; Wang, Yifei; Li, Chen; Wang, Xianli; Yang, Ruiyun; Xiao, Xinguang (Frontiers in Medicine, 2023)
Background and Purpose Early diagnosis is important for treatment and prognosis of obstructive sleep apnea（OSA）in children. Polysomnography（PSG）is the gold standard for the diagnosis of OSA. However, due to various reasons, such as inconvenient, high cost, etc, it is less used in children, especially in young children. This study aims to establish a new diagnostic method with imaging data of upper airway and clinical signs and symptoms. Methods In this restrospectiv study ,clinical and imaging data were collected from children ≤ 10 years old who underwent nasopharynx CT scan(low-dose protocol)from February 2019 to June 2020,including 25 children with OSA and 105 non-OSA. The informatin of the upper airway (A-line; N-line; nasal gap; upper airway volume; upper and lower diameter, left and right diameter and cross-sectional area of the narrowest part of the upper airway) were measured in transaxial , coronal and sagittal images. The diagnosis of OSA and adenoid size were given according to the guidelines and consensus of imaging experts.The information of clinical signs, symptoms and others were obtained from medical records. According to the weight of each index on OSA, the indexes with statistical significance were screened out, then were scored and summed up. ROC analysis was performed with the sum as the test variable and OSA as the status variable to evaluate the diagnostic efficacy on OSA. Results The AUC of the summed scores of upper airway morphology and clinical index for the diagnosis of OSA was 0.984 (95% CI 0.964-1.000). When sum=7 was used as the threshold (participants with sum>7 were considered to have OSA), the Youden’s index reached its maximum at which point the sensitivity was 88.0%, the specificity was 98.1%, and the accuracy was 96.2%. Conclusion The morphological data of the upper airway based on CT volume scan images combined with clinical indices have high diagnostic value for OSA in children; CT volume scanning plays a great guiding role in the selection of treatment scheme of OSA.It is a convenient, accurate and informative diagnostic method with a great help to improving prognosis.